Role of Endothelin 1 on Proliferation and Migration of Human MCF-7 Cells - Cinar, Irfan; Yayla, Muhammed; Bilen, Arzu; Bayraktutan, Zafer; Çelik, Muhammet (AVES YAYINCILIK A.Ş., 2020)
The aim of this study was to explore the role of endothelin 1 (ET-1) in human breast cancer proliferation and migration and antagonism of endothelin receptor A (ETAR) and endothelin receptor B (ETBR) by using the non-selective dual ETA/ETB receptor antagonist bosentan and determine its anti-proliferative, anti-metastatic, and apoptotic effects demonstrated by nuclear factor kappa B (NF-kB), vascular endothelial growth factor (VEGF), Caspase 3 and Caspase 9 expression on endothelin-induced proliferation of MCF-7 cell line in vitro.A total of 8,000 cells were seeded into e-plates 24 hours after the cells were incubated with or without 10-4 M BOS (1 hour before ET-1 treatment); 10-7, 10-8, and 10-9 M ET-1 for 1-4 days.Whether ET-1 is present or not in the tumor area, bosentan exerts anti-proliferative effect on breast cancer. However, ET-1 and bosentan group showed important inhibitory effect on tumor migration compared to bosentan alone, which can be attributed to increased activity of ET-1 axis in the presence of ET-1. The imbalance among the NF-kB, caspases, and VEGF, which are predictive factors of carcinogenesis significantly improved after bosentan administration.Our study definitely demonstrated ET-1 and its critical role in cancer progression with apoptotic and anti-apoptotic pathways (NF-κB) and VEGF expression, and migration analyses were also performed. The second major finding was that bosentan inhibited ET-1-mediated effects on tumor proliferation and migration.
Keywords: Medicine (General); R5-920; 3. Good health